Novel mutations of the X-linked genes associated with early-onset high myopia in five Chinese families - Feiyin Zi; Zhen Li; Wanyu Cheng; Xiaoyu Huang; Xunlun Sheng; Weining Rong (BMC, 2023)
Abstract Purpose To report novel pathogenic variants of X-linked genes in five Chinese families with early-onset high myopia (eoHM) by using whole-exome sequencing and analyzing the phenotypic features. Methods 5 probands with X-linked recessive related eoHM were collected in Ningxia Eye Hospital from January 2021 to June 2022. The probands and their family members received comprehensive ophthalmic examinations,and DNA was abstracted from patients and family members. Whole-exome sequencing was performed on probands to screen the causative variants, and all suspected pathogenic variants were determined by Sanger sequencing and co-segregation analysis was performed on available family members. The pathogenicity of novel variants was predicted using silico analysis and evaluated according to ACMG guidelines. RT-qPCR was used to detect differences in the relative mRNAs expression of candidate gene in mRNAs available with the proband and family members in the pedigree 2. The relationship between genetic variants and clinical features was analyzed. Results All probands were male, and all pedigrees conformed to an X-linked recessive inheritance pattern. They were diagnosed with high myopia at their first visits between 4 and 7 years old. Spherical equivalent ranged between − 6.00D and − 11.00D.The five novel hemizygous variants were found in the probands, containing frameshift deletion variant c.797_801del (p.Val266Alafs*75) of OPN1LW gene in the pedigree 1, nonsense variant c.513G > A (p.Trp171Ter)of RP2 gene in the pedigree 2, missense variant c.98G > T (p.Cys33Phe) of GPR143 gene in the pedigree 3, frameshift deletion variant c.1876_1877del (p.Met626Valfs*22) of FRMD7 gene in the pedigree 4 and inframe deletion variant c.670_ 675del (p.Glu192_ Glu193del) of HMGB3 gene in the pedigree 5. All variants were classified as pathogenic or likely pathogenic by the interpretation principles of HGMD sequence variants and ACMG guidelines. In family 2, RT-qPCR showed that the mRNA expression of RP2 gene was lower in the proband than in other normal family members, indicating that such variant caused an effect on gene function at the mRNA expression level. Further clinical examination showed that pedigrees 1, 2, 3, and 4 were diagnosed as X-linked recessive hereditary eye disease with early-onset high myopia, including quiescent cone dysfunction, retinitis pigmentosa, ocular albinism, and idiopathic congenital nystagmus respectively. The pedigree 5 had eoHM in the right eye and ptosis in both eyes. Conclusion In this paper,we are the first to report five novel hemizygous variants in OPN1LW, RP2, GPR143, FRMD7, HMGB3 genes are associated with eoHM. Our study extends the genotypic spectrums for eoHM and better assists ophthalmologists in assessing, diagnosing, and conducting genetic screening for eoHM.